2022
DOI: 10.3390/app12020916
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Changes in Diverse Orthodontic Looms: A Systematic Review and Meta-Analysis

Abstract: Upper airway assessment is particularly important in the daily work of orthodontists, because of its close connection with the development of craniofacial structures and with other pathologies such as Obstructive Sleep Apnea Syndrome (OSAS). Three-dimensional cone-beam computed tomography images provide a more reliable and comprehensive tool for airway assessment and volumetric measurements. However, the association between upper airway dimensions and skeletal malocclusion is unclear. Therefore, the current sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In this regard, aging could negatively influence the effectiveness of the treatment due to the deterioration of the structure and function of the superior airway. With aging, the hypoxic response during sleep decreases, the breathing muscles have less tensile strength and fatigue resistance [ 31 , 32 ], the ventilatory system during sleep is more unstable [ 33 ], the strength of the upper airway dilatator muscle reduces, and the pharyngeal closing pressure and upper airway resistance and laxity increase [ 34 ]. One study [ 34 ] found a progressive long-term (10 years) reduction of the efficacy of the treatment after the initial reduction of AHI values at 1 year and 2 years follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, aging could negatively influence the effectiveness of the treatment due to the deterioration of the structure and function of the superior airway. With aging, the hypoxic response during sleep decreases, the breathing muscles have less tensile strength and fatigue resistance [ 31 , 32 ], the ventilatory system during sleep is more unstable [ 33 ], the strength of the upper airway dilatator muscle reduces, and the pharyngeal closing pressure and upper airway resistance and laxity increase [ 34 ]. One study [ 34 ] found a progressive long-term (10 years) reduction of the efficacy of the treatment after the initial reduction of AHI values at 1 year and 2 years follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical implications of changes in pharyngeal airway dimensions following premolar extractions warrant careful consideration. Orthodontists must balance the desired dental and skeletal outcomes with potential effects on the upper airway, particularly in patients with preexisting respiratory conditions [ 17 ]. The statistically significant reduction in airway volume in both extraction groups may raise concerns about the potential impact on respiratory function and highlights the importance of thorough patient assessments and collaborative decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…It may determine a clockwise rotation of the mandible and a vertical type of growth [17]. Depending on the position of the tongue and its action on the floor of the mouth, two types of anomalies can develop: Angle class II, with the tongue in a lower and posterior position, and Angle class III, with the tongue in a lower and anterior position [17][18][19][20][21]. An enlarged lower floor, dental crowding, difficulties in swallowing and mastication, the upper incisors proclinated and lower ones lingualized, and a deep Diagnostics 2024, 14, 903 2 of 10 palatal vault are also mentioned as complications of the altered tongue position [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Their sample consisted of 36 cleft lip and palate subjects and 30 subjects without cleft lip and palate in the control group [22]. A meta-analysis [20] in 2022 aimed to evaluate scientific evidence related to the effects of different orthodontic treatment possibilities on the airways. The authors included in their meta-analysis 66 eligible articles about the CT and CBCT airway evaluation after orthodontic therapy [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation